The Multiple Effects of Procurement Price on Production and Procurement of Wheat in Pakistan (The Pakistan Development Review, 1989)
An increase in the procurement price affects government procurement of wheat in at least four ways. Properly estimating the total effect requires taking account of both the direct effects of an increased share of marketed surplus being procured and the indirect effects through the impact on production, marketed surplus, and the wholesale price. Estimates are that a real one-rupee increase per 40 kilograms - approximately 1.25 percent - will raise procurement by about 90 thousand tons.